Law and the Fool - Nicole Rogers (Law Text Culture, 2010)
The Fool historically occupied a unique and privileged position. Accustomed and indeed required to deride the ruler and poke fun at the state, he remained immune from any form of punitive retribution. My focus in this article is on the antics of contemporary Fools and the extent to which the state’s response to such antics is circumscribed. I shall analyse the contemporary Fool’s satirical and playful activities as one form within the broad spectrum of performances of resistance to the authority of the state. Playful, satirical and/or carnivalesque performances of the Fool, in which the state is held up for ridicule without any suggestion of violence, are at one end of this spectrum; at the other end are performances of law-making violence such as contemporary acts of terrorism which, if successful, comprise the ‘ungraspable revolutionary instant’ during which a new state is constituted (Derrida 1990: 1001).